1995
DOI: 10.1161/01.cir.92.9.2385
|View full text |Cite
|
Sign up to set email alerts
|

Pressure- and Volume-Induced Left Ventricular Hypertrophies Are Associated With Distinct Myocyte Phenotypes and Differential Induction of Peptide Growth Factor mRNAs

Abstract: PO- and VO-induced LV hypertrophies are associated with distinct molecular phenotypes and patterns of peptide growth factor induction. Stimulus-specific heterogeneity in the signaling events and peptide growth factors coupled to gene expression could play a role in determining the type of hypertrophy that is caused by various forms of hemodynamic overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
3
8

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 37 publications
9
78
3
8
Order By: Relevance
“…In concentric LV hypertrophy, cardiomyocytes grow in a transverse direction while maintaining a constant cell length, whereas in eccentric hypertrophy, cardiomyocytes grow proportionally in longitudinal and transverse directions. This difference in cardiomyocyte remodeling correlates with distinct patterns of peptide growth factor induction in both conditions [9]. As shown in our studies, different correlation exists between cardiomyocyte hypertrophy and fibrosis in HFREF and HFREF patients [39].…”
Section: Cardiomyocyte Level: Structural and Functional Alterations Isupporting
confidence: 69%
“…In concentric LV hypertrophy, cardiomyocytes grow in a transverse direction while maintaining a constant cell length, whereas in eccentric hypertrophy, cardiomyocytes grow proportionally in longitudinal and transverse directions. This difference in cardiomyocyte remodeling correlates with distinct patterns of peptide growth factor induction in both conditions [9]. As shown in our studies, different correlation exists between cardiomyocyte hypertrophy and fibrosis in HFREF and HFREF patients [39].…”
Section: Cardiomyocyte Level: Structural and Functional Alterations Isupporting
confidence: 69%
“…Although the underlying mechanism by which E 2 prevented the increase of LVEDP remains undetermined, a role for nitric oxide may be postulated. In the myocardium, nitric oxide has been shown to increase diastolic distensibility (Prendergast et al, 1997;Paulus et al, 1994), and nitric oxide synthase activity in the heart can be enhanced by oestrogen treatment (Neudling et al, 1999) A sustained increase in systolic load, as observed in systemic hypertension leads to a concentric pattern of cardiac hypertrophy, characterized by the increased expression of the putative hypertrophic marker prepro-ANP mRNA and the progression of interstitial ®brosis (Boluyt & Bing, 1995;Calderone et al, 1995;Weber & Brilla, 1991;Grossman et al, 1975). Direct morphological examination was not performed to determine whether a concentric pattern of cardiac remodelling had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…130 Pressure and volume stress induce distinct molecular responses; despite a similar degree of hypertrophy and ANP induction, marked differences in the expression levels of ␤-myosin, ␣-skeletal actin, and SERCA2a were observed in pressure overload-induced hypertrophy relative to volume overload. 131 Taken together, hypertrophic signaling can be viewed as a web that integrates and modulates a multitude of input signals (Figure). Whereas multiple endogenous and exogenous inhibitors of cardiac hypertrophy have been identified, it will be critical to specifically target "pathological" hypertrophy while preserving the heart's ability to adapt to an increase in physiological demands.…”
Section: Physiological Versus Pathological Hypertrophymentioning
confidence: 99%